2019
DOI: 10.1049/iet-esi.2019.0031
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid active load and ideal synchronous condenser‐based model for STATCOM applied to power flow studies

Abstract: This study proposes a generalised STATCOM model employing active load and ideal synchronous condenser representation and its related power flow solution. The proposed method considers the effects of DC side voltage, internal switching losses, and operation mode on the power flow problem. To such aim, the proposed model tackles with a tap changing transformer accompanied by a variable conductance at the DC side in order to model the switching losses. This model can also take into account voltage regulation, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A considerable number of publications have been made on cascaded multilevel converters [31,38,39,41,44,45,48,67]. As shown in Figure 3, good work has been written on VSC [30,35,37,43,52,57,64], PWM [28,46,58,59,60], MMC [40,49,62,63,66,73], software-based [32,47,53,71,72], and load flow models [50,51,54,68,70], as shown in Figure 3. Some papers on multilevel converters [33,56], cascaded multilevel inverters [34,55], multilevel inverters [69], VSI [36], hexagram converters [42], and novel techniques [29,61,65] have been observed.…”
Section: Different Aspects Of Statcom Modellingmentioning
confidence: 99%
“…A considerable number of publications have been made on cascaded multilevel converters [31,38,39,41,44,45,48,67]. As shown in Figure 3, good work has been written on VSC [30,35,37,43,52,57,64], PWM [28,46,58,59,60], MMC [40,49,62,63,66,73], software-based [32,47,53,71,72], and load flow models [50,51,54,68,70], as shown in Figure 3. Some papers on multilevel converters [33,56], cascaded multilevel inverters [34,55], multilevel inverters [69], VSI [36], hexagram converters [42], and novel techniques [29,61,65] have been observed.…”
Section: Different Aspects Of Statcom Modellingmentioning
confidence: 99%
“…It is worth noting that since the virtual bus j is only connected to bus i, then derivative terms of P and Q of all buses expect for bus i are equal to zero. By excluding the row related to injected reactive power and the column related to voltage magnitude, the modified version of (4) and (5) under the voltage control mode are obtained as (7) and (8), respectively. In comparison with (4), it can be concluded that the proposed approach has just led to the changes in equations associated to the active and reactive powers of bus i…”
Section: Voltage Control Modementioning
confidence: 99%
“…In contrast to the LCC-HVDC transmission systems, the VSC-HVDC system uses the voltage source converters (VSCs). If the DC side of VSC is equipped with the active power energy source, generation and absorption of both active and reactive powers, can be provided [6,7]. To exchange the reactive power with the AC grid, the pulse width modulation (PWM) shifts the output current to the lead or lag the terminal voltage based on the system requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The static synchronous compensators (STATCOM) have been widely researched in medium-voltage and high power applications [1], [2]. Conventionally, the STATCOM is applied to compensate for the reactive current and solve the power quality issues in the distribution power grid [3].…”
Section: Introductionmentioning
confidence: 99%